AGE AND GROWTH OF THREE SPECIES OF SEERFISHES SCOMBEROMORUS COMMERSOU, S. GUTTATUS AND S. L1NEOLATUS - Devaraj, M (Indian Journal of Fisheries, 2011)
Length-frequency an:(lysis indicates that the king seer (Scomberomorus cotnmerson)attains a size of 402 mim, 726 mm, 995 mm and 1186 mm total lengthat 1, 2, 3, and 4 years of age, respectively, the streaked seer (S. Uneolatus) reachesa size of 350 mm, 713 mm, 835 mm and 965 mm total length et 1, 2, 3 and4 years, respectively, and the spotted seer (S. guttatus a size of 369 mm, 532mm: and 640 mm at 1, 2, and 3 years, respectively. Back-calculated lengths of fishat the time of ring formation on otoliths figree closely with the results of lengthfrequencyanalysis. The maximum lengths of king seer, streaked seer and spottedseer met with in the catches are 1936 mm (33 kg), 980' mm (4.6 kg) and 705mm (2.1 kg), respectively. The theoretical maximum lengths (Lac) computed byBagenal or Rafail method for the von Bertsfeaffy growth equation are found to be2081 mm (46.7 kg) for the king seer, 1683 mm (15.7 kg) for the male streakedseer, 1447 ram (24.3 kg) for the female streaked seer and 1278 mm (9.6 kg) forthe spotted seer. All the three species develop two rings a year in their otolithsat a regular interval of six months. For all the three species, the exponent in thelength-weight relationship is found to be close to 3.